The Improvement of Students Speaking Skill by Using High Order Thinking Skills (HOTS) Method at MA. Al-Huda Sumber Nangka Desa Duko Timur Kecamatan Larangan Kabupaten Pamekasan - Dinar V`incy Yunitaka Bahrudin; Moh Soheh; Siti Mukamilah (Penerbit STKIP PGRI Bangkalan, 2020)
English as a foreign language make students in Indonesian faced some difficulties in understanding the meaning and structure of language. This condition also happen at MA Al Huda Sumber Nangka Pamekasan. To overcomethis basic problems, so teacher need a good method in their teaching process especially in speaking that is have an important roles in mastering language. 2013 curriculumrevision implemented High Order Thinking Skill (HOTS) method. The purpose of this research is to know the factors that affected students low mastery of English and to describe headmaster and teachers point of view about the implementation of HOTS method in students mastery. The research design of this research was used descriptive qualitative. Researcher used observation, interview, questionnaire and documentation asinstrument in data collection. After got the data,researcher analyzed the data by using Miles and Huberman. The result showed that factors which make students have a low speaking ability are students attitude, motivation to study well and also lack of parental supervision of students learning outcome. Headmaster and teacher very appreciate with the implementation of 2013 curriculum revision in order to increase education quality. It can be prove that students speaking skill at MA AlHuda better than before by using HOTS method.